Environment and natural resource management in Bangladesh - Sadeque, Syed Zahir; Bangladesh Sociological Association ([Dhaka] : Bangladesh Sociological Association, 1992)
Papers presented at a workshop held on 25-26 January 1991.
Includes bibliographical references.
Keywords: Natural resources -- Bangladesh -- Management -- Congresses; Environmental protection -- Bangladesh -- Congresses